2012
DOI: 10.4103/2152-7806.103878
|View full text |Cite
|
Sign up to set email alerts
|

Giant cell reparative granuloma of the sphenoid: Case report and review of the literature

Abstract: Background:Giant cell reparative granulomas (GCRGs) are rare lesions in the cranial bones. We present a case of this rare lesion emanating from the clivus and replacing the sphenoid sinus, a highly unusual location for this entity.Case Description:The case and clinical course of a 29-year-old female who presented with a large sphenoid mass are described here. The patient presented with symptoms of severe headache and diplopia; imaging demonstrated a large sphenoid mass which was completely resected via an endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 20 publications
(47 reference statements)
2
26
0
1
Order By: Relevance
“…The histologic ndings of CGCG, Giant Cell Tumor (GCT) and brown tumor of hyperparathyroidism have virtually identical histologic features and closely resembles granulomas. Immunohistochemical studies have reported CGCG positive for CD 68 [5,6]. In our study also, 4 cases of Immunohistochemistry were positive for CD 68.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…The histologic ndings of CGCG, Giant Cell Tumor (GCT) and brown tumor of hyperparathyroidism have virtually identical histologic features and closely resembles granulomas. Immunohistochemical studies have reported CGCG positive for CD 68 [5,6]. In our study also, 4 cases of Immunohistochemistry were positive for CD 68.…”
Section: Resultssupporting
confidence: 74%
“…Histological examination of CGCG suggests the lesions are composed of hypercellular brous stroma containing numerous multinucleated giant cells within the background of mononuclear stromal cells and spindle shaped broblasts along with areas of hemorrhages or foci of cystic degeneration and osteoid production [5,6,7,10,11,12]. The histologic ndings of CGCG, Giant Cell Tumor (GCT) and brown tumor of hyperparathyroidism have virtually identical histologic features and closely resembles granulomas.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations